A Highly Efficient NHC-Catalyzed Aerobic Oxidation of Aldehydes to Carboxylic Acids - Khatana, Anil Kumar; Singh, Vikram; Gupta, Manoj Kumar; Tiwari, Bhoopendra (Synthesis, 2018)
An N-heterocyclic carbene (NHC) organocatalytic aerobic oxidation of aldehydes to the corresponding carboxylic acids is explored. Remarkably, this method allows for efficient conversion of different classes of aldehydes including highly challenging electron-rich aryl aldehydes, ortho-substituted aryl aldehydes, various heteroaromatic aldehydes and α,β-unsaturated aldehydes under mild reaction conditions. These substrates, under previously reported NHC-catalyzed methods, are typically unreactive or give poor yields, require high reaction temperatures and reaction times of several days.
Keywords: carboxylic acids; aldehydes; N-heterocyclic carbenes; aerobic oxidation; organocatalysis